Improving the Methodology for Identifying Mild Cognitive Impairment in Intellectually High-Functioning Adults Using the NIH Toolbox Cognition Battery - Iverson, Grant L.; Karr, Justin E. (Frontiers in Psychology, 2021)
Objective: Low scores on neuropsychological tests are considered objective evidence of mild cognitive impairment. In clinical practice and research, it can be challenging to identify a cognitive deficit or mild cognitive impairment in high-functioning people because they are much less likely to obtain low test scores. This study was designed to improve the methodology for identifying mild cognitive impairment in adults who have above average or superior intellectual abilities. Method: Participants completed the National Institutes of Health Toolbox for the Assessment of Neurological and Behavioral Function Cognition Battery (NIHTB-CB). The sample included 384 adults between the ages of 20 and 85 who had completed either a 4-year college degree or who scored in the above average, superior, or very superior range on a measure of intellectual functioning, the Crystallized Composite score. Algorithms were developed, based on the absence of high scores and the presence of low scores, for identifying mild cognitive impairment. Results: Base rate tables for the presence of low scores and the absence of high scores are provided. The base rate for people with high average crystalized ability obtaining any one of the following, 5 scores <63rd percentile, or 4+ scores <50th percentile, or 3+ scores ≤ 25th percentile, or 2+ scores ≤ 16th percentile, is 15.5%. Conclusions: Algorithms were developed for identifying cognitive weakness or impairment in high-functioning people. Research is needed to test them in clinical groups, and to assess their association with clinical risk factors for cognitive decline and biomarkers of acquired neurological or neurodegenerative diseases.